Effectiveness and safety of 0.5% timolol solution in the treatment of pyogenic granuloma: A randomized, double-blind and placebo-controlled study - Patra, Aparesh Chandra; Sil, Amrita; Ahmed, Sk. Shahriar; Rahaman, Sufiur; Mondal, Nasiruddin; Roy, Sudipta; Datta, Adrija; Kaliyadan, Feroze; Panda, Saumya; Setia, Maninder Singh; Dogra, Sunil; Khandpur, Sujay; et al. (Indian journal of dermatology, venereology, and leprology, 2022)
Introduction Pyogenic granulomas are benign vascular lesions of the skin and mucosa which are often a source of concern because of their recurrent bleeding even with minimal trauma. Current treatment for pyogenic granuloma is ablative; no medical therapy is standardized to date. Timolol, due to its vasoconstrictive effect, vascular growth factor inhibition and apoptosis promotion properties, is a potential therapeutic option. Objectives: To assess the effectiveness and safety of topical timolol in the treatment of pyogenic granulomas. Methods A two-centre, double-blind and placebo-controlled trial (Registration CTRI/2019/04/018581) was conducted. Patients of either sex were recruited with pyogenic granuloma lesions of less than eight weeks duration. Topical treatment with 0.5% timolol or matching glycerin placebo was continued for six weeks. Changes in color, size, bleeding tendency, physicians' and patients' global assessments and adverse events were assessed. Results Forty subjects were randomized between the two groups which were comparable in age, sex, duration of illness and baseline lesion size.Significant improvement was noted with timolol, with color change from first follow-up onwards and lesion size reduction from second follow-up onward. Patients' assessment of bleeding tendency also showed imrovement from the second visit onward. Between-group comparison showed significant difference with respect to percentage reduction in size (timolol 40.9%, placebo 3.4%; P = 0.002). Rescue treatment (electrosurgery) was required in five patients on placebo and in one in the timolol group (P = 0.182). Complete resolution occurred in 2 (10%) patients with timolol and in no patients on placebo (P = 0.231). Limitations: We observed effects of treatment for only six weeks. Conclusion Topical timolol may be a treatment option for early pyogenic granulomas but complete resolution is unlikely in six weeks. Studies of longer duration are required to assess resolution and recurrence rates.